2021
DOI: 10.3390/biology10050392
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics-Based Identification of Salivary Changes in Patients with Burning Mouth Syndrome

Abstract: Burning mouth syndrome (BMS) is a chronic oral condition characterized by an intraoral burning sensation, taste alterations, and dry mouth sensations. Although a number of factors have been closely related to the appearance of the symptoms, including anxiety, depression, and sleep disturbances, the etiology of BMS remains unclear. Furthermore, currently no objective diagnostic tools exist, making its diagnosis challenging. Therefore, to contribute to the knowledge about BMS etiology and look for objective tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
0
13
1
Order By: Relevance
“…This resulted in 33 possible references. After reading the full‐text articles, 16 references were discarded for the following reasons: one for not having a CG (Kang et al, 2017), one for not analyzing biomarkers (Castillo‐Felipe et al, 2021), two for being letters to the editor (Boras et al, 2006; López‐Jornet et al, 2009), four for evaluating genetic polymorphisms (Campello et al, 2020; Guimarães et al, 2006; Kim et al, 2017; Vucićević‐Boras et al, 2003), five for not clarifying the diagnostic criteria used for BMS (Hershkovich & Nagler, 2004; Loeb et al, 2008; Simcić et al, 2006; Srinivasan et al, 2008; Suh et al, 2009), and three for not presenting numerical values for biomarker levels (Acharya et al, 2019; Ji et al, 2017; Kho et al, 2013; these values were requested from the authors, and no response was obtained). Finally, 17 studies were included in this systematic review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…This resulted in 33 possible references. After reading the full‐text articles, 16 references were discarded for the following reasons: one for not having a CG (Kang et al, 2017), one for not analyzing biomarkers (Castillo‐Felipe et al, 2021), two for being letters to the editor (Boras et al, 2006; López‐Jornet et al, 2009), four for evaluating genetic polymorphisms (Campello et al, 2020; Guimarães et al, 2006; Kim et al, 2017; Vucićević‐Boras et al, 2003), five for not clarifying the diagnostic criteria used for BMS (Hershkovich & Nagler, 2004; Loeb et al, 2008; Simcić et al, 2006; Srinivasan et al, 2008; Suh et al, 2009), and three for not presenting numerical values for biomarker levels (Acharya et al, 2019; Ji et al, 2017; Kho et al, 2013; these values were requested from the authors, and no response was obtained). Finally, 17 studies were included in this systematic review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the hypothesis of local inflammation was supported by enhanced levels of salivary cytokines, despite inconstantly demonstrated for interleukins (IL-1β, IL-18, 31,42,84 IL-6, 81,83 and IL-2 81 ) and molecules involved in innate immunity. 17,35,58…”
Section: Introductionmentioning
confidence: 99%
“…Regarding saliva composition, in a recent study authors compared the proteomic profile of the saliva of BMS patients with that of healthy controls, using electrophoresis, demonstrating the higher presence, in BMS patients, of proteins associated with important signaling pathways such as those that regulate inflammation, stress and the immune system [62]. Using the same methodology other authors suggested that neurotrophin signaling pathway could be involved in the pathophysiology of BMS by increasing neural apoptosis within the oral mucosa [63].…”
Section: Saliva Compositionmentioning
confidence: 99%